Flexible Ureterorenoscopy for Treating Kidney Stones > 2 cm; Effectiveness and Complications - Ibrahim, Mohammed Abdulkareem; Shamsodini, Ahmad; Ali, Omar; Salah, Morshed Ali; Nikoghosyan, Samvel; Alshrani, Muammer Mohamed Ibrahim (Archives of Clinical and Medical Case Reports, 2022)
Objective: To present a single center experience using FURS in the field of larger kidney stones, we conducted this study. The continuous improvement in technology has made the FURS associated with less complication rate and comparative SFR to PCNL in treating kidney stones > 2-cm in size. Material and methods: 30 patients were candidates for this retrospective study. They were grouped into 2-groups, Group A, patients with stone size between 2–2.5-cms. Group-B patients with stone size ≥ 2.6 -cm. Effectiveness was measured in terms of the number of sessions and the time needed to reach the stone free rate (SFR), and the reported procedure- associated serious complications. The follow-up period extended up to 24- months. Results: SFR within 6- months was unremarkably different between the groups, 72.8%, 62.5% for G-A and G-B respectively. There was a considerably larger percentage of patients in G-B who were not cleared from the stones after 6- months, 37.5% VS 9% for G-A. The same trend between the two groups also seen in the number of sessions performed. However, the average procedure time was significantly less in G-A. The rate of complication was not increased as the stone size increases. Conclusion: FURS is a safe, less morbid, and effective tool of treatment that could replace PCNL in treating kidney stone > 2-cm. The time needed to reach stone-free status and the average procedure time should be taken into consideration. Future development in clearing stone fragments might push less invasive procedures to take the lead.